Radioelectric Asymmetric Conveyed Fields and Human Adipose-Derived Stem Cells Obtained with a Nonenzymatic Method and Device: A Novel Approach to Multipotency. Issue 12 (December 2014) - Maioli, Margherita; Rinaldi, Salvatore; Santaniello, Sara; Castagna, Alessandro; Pigliaru, Gianfranco; Delitala, Alessandro; Bianchi, Francesca; Tremolada, Carlo; Fontani, Vania; Ventura, Carlo
Human adipose-derived stem cells (hASCs) have been recently proposed as a suitable tool for regenerative therapies for their simple isolation procedure and high proliferative capability in culture. Although hASCs can be committed into different lineages in vitro, the differentiation is a low-yield and often incomplete process. We have recently developed a novel nonenzymatic method and device, named Lipogems, to obtain a fat tissue derivative highly enriched in pericytes/mesenchymal stem cells by mild mechanical forces from human lipoaspirates. When compared to enzymatically dissociated cells, Lipogems-derived hASCs exhibited enhanced transcription of vasculogenic genes in response to provasculogenic molecules, suggesting that these cells may be amenable for further optimization of their multipotency. Here we exposed Lipogems-derived hASCs to a radioelectric asymmetric conveyer (REAC), an innovative device asymmetrically conveying radioelectric fields, affording both enhanced differentiating profiles in mouse embryonic stem cells and efficient direct multilineage reprogramming in human skin fibroblasts. We show that specific REAC exposure remarkably enhanced the transcription of prodynorphin, GATA-4, Nkx-2.5, VEGF, HGF, vWF, neurogenin-1, and myoD, indicating the commitment toward cardiac, vascular, neuronal, and skeletal muscle lineages, as inferred by the overexpression of a program of targeted marker proteins. REAC exposure also finely tuned the expression of stemness-related genes, including NANOG, SOX-2, and OCT-4. Noteworthy, the REAC-induced responses were fashioned at a significantly higher extent in Lipogems-derived than in enzymatically dissociated hASCs. Therefore, REAC-mediated interplay between radioelectric asymmetrically conveyed fields and Lipogems-derived hASCs appears to involve the generation of an ideal "milieu" to optimize multipotency expression from human adult stem cells in view of potential improvement of future cell therapy efforts.